Online Study Satisfaction of Accounting Students in Thailand during COVID-19 Pandemic - Adulyadej Tunkaew; Sujittra Hongyon; Chonticha Chuasuwan; Wiranya Sutthikun; Sirirak Meesri (Cita Konsultindo Research Center, 2023)
This research aimed to examine online study satisfaction of college students in Ubon Rathchathani province, Thailand and to compare their satisfaction in online study during COVID-19 pandemic according to personal factors. The population in this research was college students accounting major from Ubon Ratchathani province, the sample group was 380 people selected by cluster sampling method. Research instrument was questionnaire with 5 level of rating scale, CVI at .86. The statistics used in research were percentage, mean, standard deviation, t-test, and f-test. The research showed that college students had high level of satisfaction on study online during COVID-19 pandemic thus consider from every aspects that contain high level of satisfaction. The average scores descending were educational aspect, utilization aspect, and technology aspect.